(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Banana is a very important staple food corp in Tamil Nādu. It is grown is every part of the country with the largest cultivating and marketing recorded is south Tamil Nādu especially Tirunelveli District, in Radhapuram thaluk Village. However, Banana Marketing process very big challenges to formers and small-scale cultivators. In this review different methods of natural controlled methods. Media technologies the commonly used research approaches involved collecting data from people through interview